Pendidikan Agama Islam Dan Tantangannya: (Studi Perkembangan Pendidikan Berbasis Agama Islam Di Kota Jayapura) - Iribaram, Suparto (POROS ONIM: Jurnal Sosial Keagamaan, 2020)
This article aims to find out about Islamic education and the challenges in its implementation in Jayapura City. The method of data collection was carried out by interviews, observation and FGD (Focus Group Discussion). The data which has been classified are made narrative by giving an interpretation and data display. The results of this study found that religious education in non Muslim majority areas like Jayapura is facing serious challenges. Besides it demanded to give contribution, Islamic education must be able to adapt with others religious group. For Muslims internal it becomes something that should be implemented, they should performance activities that also respect to other religions and also expected to give contribution in actualizing human being who are able to compete in global world but also still on the values of submission to Allah SWT. For that reason, Islamic education in Jayapura must be adapt with the religious life conditions where it can create a harmony and peaceful life of people and Islamic education are also required to arrange the fundamental change steps and seek innovative alternative education models.